STAPHYLOCOCCAL INFECTION IN DOGS (DIAGNOSIS, TREATMENT AND PREVENTION) - V. B. Rudenko; P. A. Rudenko; S. G. Semushina; I. A. Pakhomova (Ветеринария сегодня)
The paper provides characteristics of diagnostic methods, treatment and preventive measures for staphylococcal infection in dogs. Staphylococcal infection in dogs is an infectious disease caused primarily by staphylococcus virulent strains, characterized by various clinical forms, and it affects the dogs having defects in their immune system. Staphylococci produce a great number of pathogenicity factors (including toxins able to act independently). Therefore, it is rather difficult to apply tools of specific protection and prophylaxis. Skin and mucosa inflammation is the most common pathological condition observed in dogs. Clinical signs include: chronic septic condition with internal abscesses, different skin lesions accompanied by conjunctivitis, otitis, vulvitis, posthitis, rhinitis, sinusitis, cystitis, phlegmon, abscesses, pyometra, wound abscess, polyarthritis, gingivitis. In addition to the pathological agent, the following extra factors are needed for the disease clinical manifestation: immune deficiency, metabolic disorder, parasitic disease, manipulations resulting in damage to the skin and mucosa integrity. The fact that domestic animals can be a source of infection for people can be another reason behind an increasing interest in staphylococcal infection. A comprehensive approach is required to diagnose this disease. In addition to clinical examination, the following tests are needed biochemical blood test, bacteriological tests of biomaterials from animals, isolation of pure agent cultures and determination of sensitivity to antibacterial preparations in every particular case. Bacteriological tests are mandatory to make the final diagnosis. Treatment of dogs also requires a comprehensive approach including specific immunotherapy (active, with the use of anatoxins and antigens and passive with antistaphylococcal hyperimmune sera). Timely prevention and new approaches to treatment are crucial elements.